(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Iron from the diet is the essential part of the hemoglobin which carries oxygen in the blood, therefore, essential at all the stages of life for blood to work efficiently. Low intake of iron was found in various surveys in India by many researchers. Keeping it in view, efforts have been made to develop low cost nutritious recipes using locally available and acceptable ingredients. Organolptic evaluation of the prepared recipes has also been carried out.